Factors Related to Pulmonary Function Status of Animal Feed Industry Workers in Surabaya - Rieza Dwi Anggia (The Indonesian Journal of Occupational Safety and Health, 2020)
Introduction: Workplace air that contains dust and microorganism when inhaled by workers into respiratory tract can accumulate and cause lung function disorder. This study aimed to analyze the correlation between the concentrations of dust with the concentration of microorganism and analyze the association of worker characteristics, dust and microorganism concentration to lung physiology status. Method: This study adopted cross sectional design. The sample consisted of 24 workers who were randomly selected from factory and 10 workers who were totally selected from the administration area for respirable dust, microorganism concentration monitoring and workers’ characteristics data collecting. Result: Concentration of respirable dust has strong correlation with bacteria (rs = 0.704) and fungi (rs = 0.662) concentration. Variables that had significant association with pulmonary function status were age (p = 0.000), tenure (p = 0.008), the degree of smokers (p = 0.000), the dust concentration (p = 0.000), the bacteria concentration (p = 0.000), and the fungi concentration (p = 0.000), while the use of PPE mask (p = 0.890) had no significant association with pulmonary function status. Conclusion: Factors that related to pulmonary function status are age, tenure, degree of smokers, respirable dust, bacteria, and fungi concentration. Respirable dust concentration has significant positive correlation with bacteria and fungi concentration.Keywords: concentration of dust, concentration of microorganism, pulmonary function status